Political economy synthesis: The food policy crisis - Derrill D. Watson (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The food price crisis revealed contradictions in creating food policy. Much of the common policy response can be explained by a benevolent, unitary government. To understand the variance between countries, however, requires understanding fractured government decision-making, path dependency, and institutional constraints. Governments' relationships with the private sector are very complex. They reveal both the firms' lobbying successes as well as how the deep distrust between private and public sectors lead to perverse policy incentives and unintended consequences that undermine intended outcomes. Decision makers' private interests and riot prevention played significant roles in selected cases, but were not leading factors overall.
Keywords: Q18; H12; O13; P16; 330; political economy; food price crisis; public choice; case study